Application of the Questions Student Have to Improve Activities and Results of Learning Students - Masnur, Masnur; Usman, Muh. Abrar (Maspul Journal of English Studies, 2019)
Pusposes: This study aims to determine the increase in activities and learning outcomes of science students after using the learning model questions students have at SDN 166 Pinrang 2018/2019 academic year. Methodology: This type of research is Class Action Research. This study uses the method of observation and test methods. The instruments used were observation sheets and test questions. Based on the results obtained from this study the activity of students has increased when implementing the Questions student have learning model. Findings: In cycle 1, the average percentage of student activity was 69% while in cycle 2 it increased to 85%. The learning outcomes of students also increased, in the first cycle the classical completeness was 53.33% and in the second cycle it increased to 83.33%. Implication: The conclusion of this study is the application of the Questions Student Have learning model can improve the activities and learning outcomes of science students. The activities and learning outcomes of science students continue to increase so that they successfully meet the determined success criteria.